5/1/1968
XVIII, 436 p.
Keywords: The events of 1968 are often seen purely as a student revolution, but impacted on every aspect of French society – theatre, film, sexuality, race, the countryside, the factories. This volume explores the full diversity of this extraordinary upheaval, and shows how 1968 continues to reverberate in France today.